Mitigating fatalities and damages due to natural disasters: do human development and corruption matters? - Jaharudin Padli,; Muzafar Shah Habibullah,; Baharom Abdul Hamid,; Haslina Musa, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Studies have shown that natural disasters could pose a spectrum of challenges to human development, especially in developing countries. United Nations Development Programme (UNDP, 2004)) estimates that low human development countries accounted for more than half of reported casualties due to natural disasters for the last two decades. The study also estimates that nearly 85 percent of the people exposed to natural disasters live in either medium or low human development countries. Other related studies have shown that corrupted officials in poor countries would increase the vulnerability of these countries to natural disasters. Thus, the purpose of the present study is to investigate the impact of human development indicators, such as income per capita and human capital development (education level), as well as corruption (a measure of governance) on fatalities and damages due to natural disasters in selected 77 developing countries. By employing the two-step system GMM estimators, we identified several economic variables that are significantly related to fatalities and property damages due to natural disasters, such as flood, storm, earthquake, landslides, drought, extreme temperature, wildfire, and volcanic eruption. By exploring the impact of economic development, population density, unemployment rate, investment, government consumption expenditure, education, openness, and corruption, on disaster preparedness, it would be useful for both government and international disaster risk reduction and mitigation agencies to re-evaluate their approach towards target recipients in the future.